The book of Genesis : composition, reception, and interpretation - Evans, Craig A. (Craig Alan), 1952-; Lohr, Joel N.; Petersen, David L. (Supplements to Vetus Testamentum ;, 2012)
Drawing on the latest in Genesis scholarship, this volume offers twenty-nine essays on a wide range of topics related to Genesis, written by leading experts in the field. Topics include its formation, reception, textual history and translation, themes, theologies, and place within Judaism, Christianity, and Islam.